If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 = 15t + -17 Reorder the terms: 55 = -17 + 15t Solving 55 = -17 + 15t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-15t' to each side of the equation. 55 + -15t = -17 + 15t + -15t Combine like terms: 15t + -15t = 0 55 + -15t = -17 + 0 55 + -15t = -17 Add '-55' to each side of the equation. 55 + -55 + -15t = -17 + -55 Combine like terms: 55 + -55 = 0 0 + -15t = -17 + -55 -15t = -17 + -55 Combine like terms: -17 + -55 = -72 -15t = -72 Divide each side by '-15'. t = 4.8 Simplifying t = 4.8
| x^2+4x-170=0 | | 9x^2+92-2=0 | | 7+x=33 | | 4y=4-8/17 | | -12-2x=2x+18 | | 60/17+4y=8 | | 2(m-5)+12=3m | | 3x-9=3.5x-9 | | 2=3x^2+x-2 | | (X-1)-1.4=6.2 | | 3(x-1)=-15 | | x^2+25x=7500 | | 16-(5y-3y)=2 | | 0=3x^2+x-2 | | 11x+7.6+5x+9x-2= | | p/s-q/s=1 | | xln=-1 | | -9(x)=-63 | | 7*13*6*x=57*19 | | 4x^2+8y=40 | | 5(x-9)/2+3/4=2x+2 | | ln(2x+1)+ln(x+3)=0 | | 7+13-6+x=57-19 | | 33=x+7 | | 5=x-2/5 | | x^3-8x^2-10x+20=0 | | 3(x)=24 | | 12x+x(2-4)=0 | | 4(2-5)= | | 4y^2-96y+576=0 | | (x^2+x*y-y^2)dx(-x*y)dy=0 | | 3x^2+12x-495=0 |